Manajemen Sumber Daya Manusia Di Sekolah-Sekolah Unggulan Islam Kota Samarinda - M. Tahir; Ananiah Ananiah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
The emergence of Islamic excellent schools in the archipelago, being a cue that there will raise ghirah moslems to increase their education quality. One of efforts made in sustaining the excellence is by press pint on the Human Resources Management (read: educators and educational). In Samarinda, the existence of the Islamic excellent schools also being a trend and idol of moslem society in general, it can be seen from the society anemo to send their children to the Islamic excellent schools. This matter becomes the early inspirations in this research, by focusing the research on the efforts and strategies in the development of excellent schools of Samarinda in the case of the Human Resources. Among the Islamic excellent schools, the research objects are SD Muhammadiyah 1 and SDIT Cordova.